The Effect of Mental Pressure Due to Covid-19 on Students’ Educational Performance: A Study from Karachi, Pakistan - Khan, Aisha Rahat; Lodhi , Farida; Muneer, Rizwan; Mahmood, Huma (Utamax : Journal of Ultimate Research and Trends in Education, 2022)
Coronavirus pandemic had not only affected the physical health of people but also the mental health of people globally. It has developed a fear in the minds of people regarding their selves as well as their loved ones. The essential change in the lifestyles of people and the need for social distancing has stopped the normal activities of people which caused mental disturbance among them. The present quantitative survey-based research has been led to know the impression of COVID 19 on the mental pressure of the students regarding their academic progress. The hypothesis were developed from which one was a null hypothesis; H1, was to find that whether there is a positive relationship between mental stress and COVID and third, H2, was to find whether there is any negative relationship between mental stress and academic progress. Both, H1 and H2, were accepted through conducting quantitative research by circulating an online survey that consists of 14 close-ended questions regarding the 2 research questions made. Respondents were taken from 5 universities of Karachi, Iqra university, Jinnah university for women, NED university of Engineering and Technology, University of Karach, and ZABIST university. The samples was consist of 90 students (54) were females and (36) were male selected by simple random sampling. The statistical method used to analyze the results was the simple percentage method as it clearly defines what percentages of the students were affected by COVID and how it impacted their mental pressure. It was found that there was a positive relationship of COVID on mental pressure that means the complex spread of COVID 19, higher the mental pressure and there was a negative relationship between COVID 19 and academic performance that means that high mental pressure was the cause of the lower performance.